Authoring tool for location-based learning experiences - Zimbello, Agustina M.; Alconada Verzini, Federico Martín; Challiol, Cecilia; Lliteras, Alejandra Beatriz; Gordillo, Silvia Ethel (2017)
In this paper, we present some features of our in-situ indoor-outdoor authoring tool for location-based learning experiences. For example, how to reuse locations in different experiences or how to design from scratch in places without any location sensing mechanisms. In addition, we describe some features in which we are working on. We expect to create a space for discussion about these kind of tools and to reflect on the products created with them.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Mobile Software Engineering and Systems (4ta : 2017 : Buenos Aires, Argentina)
Keywords: AMBIENTES DE APRENDIZAJE; aprendizaje móvil